TEACHING ENGLISH WRITING FOR JUNIOR HIGH SCHOOL IN MERDEKA CURRICULUM: NARRATIVE INQUIRY - Jannah, Evi Isfiatul; Daulay, Irma Khoirot (Premise: Journal of English Education and Applied Linguistics, 2024)
This research investigates English teachers' perceptions of teaching recount text paragraphs under junior high school's Merdeka Curriculum (MC). The investigation was conducted to get more information on teachers' experiences in recount text paragraph class, primarily focusing on teacher perceptions of effectiveness, extent implementation, and recommended actions to enhance curriculum effectiveness through a narrative inquiry approach. Qualitative data were collected from two participants, Mrs. W and Mr. A, using narrative frames and structured interviews. Then, the data are analyzed using the theory from Miles, Huberman, and Saldana, involving data reduction, data display, and conclusion drawing to synthesize results. The result and discussion in this research showed that the teachers perceive MC positively in enhancing student engagement and learning outcomes in writing recount text paragraphs. The participants highlighted the curriculum's key strengths: flexibility, interactive nature, and alignment with modern teaching methodologies. Besides, the teachers also emphasized the importance of professional development, collaborative learning among teachers, and integrating learning technology to enhance curriculum effectiveness further. By investigating this topic, it gives us insights into optimizing the effectiveness of the curriculum. The optimization focuses on integrating flexible and interactive elements into the teaching process, investing in professional development for teachers, encouraging collaborative learning, and embracing learning technology tools.